Ḥāwī l-Funūn wa-Salwat al-Maḥzūn, Encompasser of the Arts and Consoler of the Grief-Stricken by Ibn al-Ṭaḥḥān : Annotated Translation and Commentary - Sawa, George Dimitri, (Islamic History and Civilization ;, 2021)
Ḥāwī l-Funūn (Encompasser of the Arts) of Ibn al-Ṭaḥḥān (d. ca. 1057) is a medieval Arabic music dictionary that complements other sources because of the practical knowledge of the author who was an accomplished singer, lutenist and composer. The first part in 80 chapters deals with compositions; voice production and characteristics, unison and duet singing, taking care of the voice; preludes, ornaments, ṭarab; the importance of tonality; approaches to teaching; musical and extra-musical behavior at the court; names of Syrian Fatimid and Ishshīdid singers. The second part in 22 chapters includes lute manufacturing, frets placement, stringing and tuning; 47 rhythmic ornaments, names and definitions of rhythmic and melodic modes; types of dances; descriptions of 12 instruments.